Cellular Immunity of Patients with Tuberculosis Combined with Diabetes - Peng Cheng; Liang Wang; Wenping Gong (Journal of Immunology Research)
Tuberculosis (TB) is one of humanity’s three major infectious diseases. Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia due to impaired insulin secretion or impaired insulin function. It has been reported that DM is a primary risk factor for TB disease. Given the increasing public health threat to people’s health, more and more studies have focused on diabetes complicated by TB. Hyperglycemia can affect the function of human immune cells, promote primary infections and reactivation of TB, and increase the susceptibility and severity of TB. However, the immunological mechanism behind it is still not clear. By reviewing the related articles on tuberculosis complicated with diabetes published in recent years, this paper expounds on the effect of hyperglycemia on innate immunity and adaptive immunity of patients with TB. This review provides new insights for elucidating the immunological mechanism of TB complicated with DM and lays the foundation for finding potential targets for preventing and treating TB combined with DM.